COVID-19 and Chagas Disease in Buenos Aires, Argentina - Fernandez, Marisa Liliana; Benchetrit, Andres; Astudillo, Osvaldo German; Garay, Alejandra M.; De Vedia, Lautaro; Garcia Bournissen, Facundo; Lloveras, Susana Cristina; Orduna, Tomas Agustín; Gonzalez, Gustavo Daniel (Frontiers in Tropical Diseases, 2022)
Coronavirus disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2. COVID-19 leads in most patients to mild-to-moderate symptoms, but some develop severe disease and death. People with medical conditions have a higher risk of death than those without them. Chagas disease (CD) can cause cardiac diseases in approximately one-third of affected people. The aim of this study is to find out if there is any clinical association between Chagas disease and COVID-19 severity. Study design: A cohort study of 29 patients hospitalized with COVID-19 and diagnosis of chronic T. cruzi infection. This coinfected cohort was matched by sex, age, presence of comorbidities and requirement of hospitalization on Intensive Care Unit (ICU) at admission, with a control cohort hospitalized due to COVID-19 without CD in a 3:1 ratio (n=87). The clinical outcomes evaluated were: days of hospitalization, death, requirement of ICU and mechanical respiratory assistance (MV). The study protocol was approved by the Institutional Ethics in Research Committee. The Chagas disease /COVID-19 coinfected cohort had a median age of 55 years old [49.0, 66.0], 17 (59%) were males. All patients survived the acute COVID-19. Three of them were admitted to the ICU and 2 required MV. Twenty-two (75.8%) required supplemental oxygen. There were not statistically differences in any laboratory parameters between groups except for LDH, which showed higher levels in co-infected cohort with a median of 573 U/L [IQR 486.00, 771.00] vs 476 U/L [346.00,641.00] in the control group(p=0.007). There were no differences in clinical outcomes between both groups. On the cohort with Chagas disease were 0 deaths, 3 (10.3%) were admitted in ICU, and 2 (6.9%) required MV, while for the control group there were 6 deaths (6.6%), 13 required ICU (14.9%) and 11 required MV (12.6%) without statistically significant difference. This small series of coinfected Chagas disease and COVID-19 does not suggest differences in clinical evolution compared to non-Chagas patients. This data is similar to a Brazilian cohort. More data of this population with and without cardiomyopathy is needed to optimize the follow up for the population affected by this neglected tropical disease about COVID-19.